Legal Protection for Healthcare Workers in The Management of Infectious Diseases Under Health Laws and Regulations - Ago Harlim; Sri Astutik; Siti Marwiyah; Wahyu Prawesthi (Green Publisher Indonesia, 2026)
In medical emergencies, healthcare workers play a vital role in controlling infectious diseases, despite facing serious social, legal, and occupational health risks. During such situations, they often cope with extreme stress, social isolation, and potential legal claims arising from the care they provide. Therefore, ensuring legal protection for healthcare providers is a fundamental element in maintaining the continuity of high-quality and balanced health services. The purpose of this paper is to examine the forms of legal protection for medical workers in managing infectious disease outbreaks as regulated under the Health Quarantine Law. This study, entitled Legal Protection for Healthcare Workers in the Management of Infectious Diseases Under Health Laws and Regulations, highlights the framework of rights and obligations for healthcare personnel, as well as the state’s responsibility in providing legal safeguards during quarantine-related interventions. The research adopts a normative legal research design, applying both statutory and conceptual approaches. Data were collected from primary legal sources, such as relevant health quarantine regulations and legislation governing medical personnel, as well as secondary sources including academic literature, scholarly journals, and expert commentaries, along with tertiary sources for supplementary context. The analysis was conducted qualitatively to provide a comprehensive understanding of how legal instruments protect healthcare workers during infectious disease outbreaks.